The concept of creativity and its essence in the training of pedagogical personnel - Ikromova Madinakhan Bakhtiyorjon kizi (Genius Publishing Group, 2025)
The article discusses the main qualities of a creative teacher in the process of training pedagogical personnel, methods for developing creativity, the importance of using this process in pedagogical education, and recommendations for forming the creative potential required of a modern teacher
Keywords: pedagogical creativity; creative thinking; innovative approach